Assessment of the Need for Construction of Cargo Ships Under Sanctions Pressure - N. V. Brikotnina (Статистика и экономика, 2024)
Purpose of the study. The main factor influencing the market for transport and logistics services in the Russian Federation in 2022 is the introduction of sanctions against the Russian Federation. As a result, consequences such as border closures, volatility in global commodity markets, and contraction in demand for goods and services have had a significant impact on the shipbuilding industry. Due to sanctions pressure and the deterioration of the technical feasibility of constructing offshore and river facilities at enterprises of the Russian Federation, the volume of potential orders has decreased. In this regard, the purpose of the study is to assess the need for the construction of cargo ships under sanctions pressure, by improving the methods of long-term forecasting.Materials and methods. The sources of information for the calculations were official data from the Federal State Statistics Service and the Russian Classification Society; forecast values from departments and analytical agencies were also used. To forecast the volume of cargo transportation by water transport, the method of multiple correlation and regression analysis was used.Results. The forecast of the volume of transportation of certain types of goods is calculated, taking into account the influence of key economic and political factors. Based on forecasts of the cargo base, exports, imports, construction, decommissioning of ships and the current state of the fleet, an assessment of the need for the construction of cargo ships under sanctions pressure until 2030 was carried out. Calculations of the need for water transport were carried out within the framework of two forecast models – optimistic and pessimistic scenarios. The optimistic one provides for further updating of vessels according to the current trend (emphasis is placed on repairs; it is assumed that only 1-2% of watercrafts will be taken out of service). The pessimistic option implies a large-scale replacement of the old cargo fleet by 2030 (with the decommissioning of all ships that have become unusable). By 2030, the demand for marine vessels will range from 452 units to 1307 units, depending on market conditions. The demand for river and river-sea vessels will range from 1433 units to 6485 units. The results of the study showed that the need for vessels stated in the Strategy is insufficient to meet the needs of the water market.Conclusion. This approach can be used when updating the development Strategy of the shipbuilding industry.